A novel aphid resistance locus in cowpea identified by combining SSR and SNP markers. (19th February 2018) - Kusi, Francis; Padi, Francis K.; Obeng‐Ofori, Daniel; Asante, Stephen K.; Agyare, Richard Y.; Sugri, Issah; Timko, Michael P.; Koebner, Robert; Huynh, Bao‐Lam; Santos, Jansen R. P.; Close, Timothy J.; Roberts, Philip A.
Abstract: The utility of combining simple sequence repeat (SSR) and single nucleotide polymorphism (SNP) marker genotyping was determined for genetically mapping a novel aphid ( Aphis craccivora ) resistance locus in cowpea breeding line SARC 1‐57‐2 and for introgressing the resistance into elite cultivars by marker‐assisted backcrossing (MABC). The locus was tagged with codominant SSR marker CP 171F/172R with a recombination fraction of 5.91% in an F2 population from 'Apagbaala' x SARC 1‐57‐2. A SNP‐genotyped biparental recombinant inbred line population was genotyped for CP 171F/172R, which was mapped to position 11.5 cM on linkage group (LG) 10 (physical position 30.514 Mb on chromosome Vu10). Using CP 171F/172R for foreground selection and a KASP‐SNP‐based marker panel for background selection in MABC, the resistance from SARC 1‐57‐2 was introduced into elite susceptible cultivar 'Zaayura'. Five BC4 F3 lines of improved 'Zaayura' that were isogenic except for the resistance locus region had phenotypes similar to SARC 1‐57‐2. This study identified a novel aphid resistance locus and demonstrated the effectiveness of integrating SSR and SNP markers for trait mapping and marker‐assisted breeding.